Evaluation levels of water quality in maeklong basin using fuzzy logic - Kanitta Sampuangthong (2018)
© 2014 IEEE. This the paper presents a model to create rule in order to divide criterion of water quality from 5 indices follows: BOD, DO, FCB, TCB and NH3 which are divided to criterion of 4 levels i.e. good, medium, bad and very bad. The data sets collected from the Maeklong basin from 9 provinces in Thailand are used more than 200 sets from 41 sampling stations. In the present study, a methodology based on fuzzy logic to assess water quality is proposed. The result from fuzzy logic is that an accuracy is approximately at 89.42%. Therefore, fuzzy logic is a suitable to use a development of effective water management plans.